Explorations in the North-West Indian Ocean: The Research Journeys of the Palinurus along the Omani Coast in the mid-1800s - Risse, Marielle (Research Expeditions to India and the Indian Ocean in Early Modern and Modern Times, 2022)
MARIELLE RISSE (Salalah) introduced us to Oman, a country in the Indian Ocean world that was never under foreign control. It is also the only country on the Arabic peninsula that gets monsoonal rains. Risse focused on the two expeditions of the brig Palinurus, which took place in the 1830s and 1850s and were the first explorations by English speakers to the southern coast of Oman, around Dhofar. The expeditions had the goal of investigating whether the Omani coast and hinterlands could be of use to the British government. They also wanted to buy the island Socotra from the Sultan in order to use it for steamship traffic between India and Britain. The surviving accounts of the expedition shed light on the local peoples; they spoke three different languages but left no written records. Risse was able to trace indigenous knowledge through oral history traditions, which were approximately 150 years old by the time they were written down in around 1850. These records reveal that much more water was available at the time, indicating that climate change is already significantly affecting Oman.
Keywords: Récits de voyage -- Oman

من وثائق األرشيف العُماني رحلة القبطان همرتون من مسقط إلى زنجبار عام 1257ه/1841م-دراسة وتحقيق - الحاتمية, فاطمة بنت ناصر بن خلف; الطرونة, محمد سالم غثيان (مجلة أبجاث ميسان, 2022)
Keywords: Récits de voyage -- Oman